Desenvolvimento sociocognitivo : relações entre teoria da mente e humor - Nogueira, Stephanie Cristine (Universidade Federal de São Carlos, 2017)
Theory-of-mind development is a process that has been investigated for decades by researchers from different fields (e.g., developmental psychologists, educators, neuroscientists and psychiatrists). A well-developed theory of mind implies the ability to attribute and understand one's own mental states and those of others, as well as to use this repertoire to explain and predict human behavior. The most significant advances in theory of mind are observed in preschool years and it is exactly at the end of this period that children begin to understand and appreciate humor. The use of humor, in turn, can not only facilitate social interactions, but can contribute to successful ones. Considering the limited number of Brazilian studies on these different aspects of child development, the main goal of the present work was to investigate the relationship between humor understanding and theory-of-mind development. Thirty-seven children, divided into two age groups (twenty 7-year-olds and seventeen 9-year-olds) and 23 adults (comparison group) participated in the present study. The instruments used were: Faux Pas Task (a theory of mind measure), one measure of sense of humor (MSHS for adults, C-MSHSC for children), and a task to assess humor appreciation, which was specifically designed for the present study. The humor appreciation task consisted in presenting participants with four jokes and four comic strips, extracted from children’s joke books and websites on comic strips directed to children. The set of selected jokes/comic strips were rated for funniness using a likert scale. Analyzes revealed differences in the pattern of preferences presented by children and adults in the humor appreciation task. More specifically, children showed more appreciation for the comic strips than adults, but no significant differences were found for joke ratings; the majority of participants rated them as "not at all funny" or "just a little bit funny”. Correlation analyses revealed a significant association between the Faux Pas total score and the MSHS score in all three age groups. More importantly, a correlation was found between children’s performance on the Faux Pas Task and their scores in one of the three C-MSHSC subscales: humor appreciation. Consistent with findings from previous studies, an age effect was found on performance in the Faux Pas Task. Results of the present study should contribute to a better understanding of the relationship between theory of mind and humor understanding, which may be, in turn, useful for the planning of interventions directed to individuals with delays in social cognition, in adverse situations or emotional pain.
Sociocognitive develoopment : relations between theory of mind and humor
Keywords: Humor; Teoria da mente; Desenvolvimento sociocognitivo; Theory of mind; Sociocognitive development; CIENCIAS HUMANAS::PSICOLOGIA